The Bifurcated Frontal Sinus - McCoul, Edward D. (OTO Open, 2018)
OBJECTIVES: Frontal sinus anatomy is complex, and multiple variations of ethmoid pneumatization have been described that affect the frontal outflow tract. In addition, the lumen proper of the frontal sinus may exist as 2 separate parallel cavities that share an ipsilateral outflow tract. This variant has not been previously described and may have implications for surgical management. STUDY DESIGN: Case series. SETTING: Tertiary rhinology practice. SUBJECTS AND METHODS: Cases with radiographic and intraoperative findings of separate parallel tracts within a unilateral frontal sinus were identified from a consecutive series of 186 patients who underwent endoscopic sinus surgery between May 2015 and July 2016. Data were recorded including sinusitis phenotype, coexisting frontal cells, and extent of surgery. RESULTS: Ten patients (5.4%) were identified with computed tomography scans demonstrating bifurcation of the frontal sinus into distinct medial and lateral lumens. All cases were treated with Draf 2a or 2b frontal sinusotomy with partial removal of the common wall to create a unified ipsilateral frontal ostium. Eleven sides had a coexisting ipsilateral agger nasi cell, 7 had a supra-agger cell, 8 had a suprabullar cell, and 1 had a frontal septal cell. There were no significant complications. CONCLUSION: The bifurcated frontal sinus is an anatomic variant that the surgeon should recognize to optimize surgical outcomes. Failure to do so may result in incomplete clearance of the sinus and residual disease. The bifurcated sinus may occur with other types of frontal sinus cells and may be safely treated with endoscopic techniques.